Prophetic Education Values In The "Udeng" Tradition (Headband Of K.H. M. Ridlwan Sururi) The Caretaker Boarding School Of An-Nur Kedungbanteng Banyumas - Zahrotun Nurur Ramadani; M. Slamet Yahya (International Journal of Education, Vocational and Social Science, 2023)
Abstract Education is a tool to raise the degree and quality of the nation. Education is also a pillar of the nation's civilization and the intellectual life of the nation. Prophetic education is a process of transferring knowledge and values which aims to get closer to God and nature and at the same time understand them to build an ideal social community (khairul ummah). The research method is a qualitative method with a descriptive approach. The values of prophetic education contained in the udeng tradition are as follows: 1) the pillars of Transcendence consist of: the relationship of monotheism. Symbolized by Udeng, the two sides of the scroll depict the two sentences of the creed and teachings from the holy book. It is symbolized that Udeng has 4 corners describing the sources of law (Quran, Hadith, Ijma, Qiyas) The Quran is a source of law as well as a way of life and teachings sourced from the holy book. 2) Liberation pillars consist of: teaching people to be able to do good wherever they are. It is symbolized by the udeng coils that go around the head as a picture of good deeds in any place and putting the interests of others first. It is symbolized by black cloth which is the basis for the traditional color of udeng. 3) Humanization pillar consists of Brotherhood. It is symbolized by udeng which must be tied tightly and live side by side. Symbolized by batik that surrounds the udeng cloth